(untitled) (Global Journal of Human-Social Science, 2022)
The article endeavours to explore the problems that the current, returning and the aspirant migrants have faced during the Covid-19 pandemic, and suggest some policies to address the problems. The article uses secondary sources of data. It finds that the pandemic has affected all employment sectors of migrants’ host countries, particularly affected those sectors where migrants are employed that have exacerbated their pre-pandemic problems. The returning and aspirant migrants have acutely faced old problems including some new ones at their communities of origins. Consequently, migration outflows and remittance inflows are affected that might impede social and economic developments of Bangladesh.